Warmer and Drier Fire Seasons Contribute to Increases in Area Burned at High Severity in Western US Forests From 1985 to 2017. Issue 22 (18th November 2020) - Parks, S. A.; Abatzoglou, J. T.
Abstract: Increases in burned area across the western United States (US) since the mid‐1980s have been widely documented and linked partially to climate factors, yet evaluations of trends in fire severity are lacking. Here we evaluate fire severity trends and their interannual relationships to climate for western US forests from 1985 to 2017. Significant increases in annual area burned at high severity (AABhs ) were observed across most ecoregions, with an overall eightfold increase in AABhs across western US forests. The relationships we identified between the annual fire severity metrics and climate, as well as the observed and projected trend toward warmer and drier fire seasons, suggest that climate change will contribute to increased fire severity in future decades where fuels remain abundant. The growing prevalence of high‐severity fire in western US forests has important implications to forest ecosystems, including an increased probability of fire‐catalyzed conversions from forest to alternative vegetation types. Plain Language Summary: The physical and ecological effects of wildfire (hereafter fire severity) have important consequences in terms of soil erosion, carbon storage, forest succession, wildlife habitat, and human safety and infrastructure. This study evaluated changes in fire severity in western US forests from 1985 to 2017 and tested whether fire severity varied with fire‐season climate. Results show that area burned at high severity increased across most of the study area, with an overall eightfold increase in western US forests from 1985 to 2017. Furthermore, warmer and drier fire seasons corresponded with higher severity fire, indicating that continued climate change may result in increased fire severity in future decades. One potential consequence of greater area burned at high severity is an increased probability that forests will convert to alternative vegetation types. Our findings provide some guidance to managers as society struggles to better coexist with fire. For example, it may be possible to increase the prevalence of low‐ and moderate‐severity fire, sometimes referred to as "good fire", through thoughtful planning about where and when to implement a less aggressive fire suppression response. Similar to prescribed fires that promote forest resilience, unplanned fires that burn during less‐than‐extreme fire seasons have the potential to serve as effective "fuel treatments". Key Points: Area burned at high severity increased from 1985 to 2017 across most western US forests coincident with warmer and drier fire seasons Warmer and drier fire seasons correspond to elevated fire severity and proportion burned at high severity across many western US forests Continued climate change could result in more high‐severity fire where fuels remain abundant